WWW: Without water warm ups - Goldsmith, W.; Sweetenham, B. (American Swimming ASCA Newsletter)
About the logical sequence of related activities to consider when thinking about an effective warm up routine for swimmers. Why warm up? Which methods for warming up? Warm down. Hydrotherapy alternatives.